OWNERSHIP STRUCTURE AND CORPORATE SOCIAL RESPONSIBILITY OF LISTED OIL AND GAS COMPANIES IN NIGERIA - Ibrahim Halidu Saidu; Saidu Amina Umar (Gusau Journal of Accounting and Finance, 2024)
The limited integration of ownership dynamics into CSR performance poses a persistent challenge in the Nigerian oil and gas industry. This study investigates the influence of ownership structure on Corporate Social Responsibility (CSR) among listed oil and gas companies in Nigeria. Using a correlational research design, data were drawn from a population of publicly listed oil and gas firms, with a final sample of 80 firm-year observations. Data were collected through content analysis of annual reports and sustainability disclosures. The analysis was carried out using descriptive statistics, correlation, and multiple linear regression, with the aid of STATA software tools. The findings reveal that all three ownership types significantly impact CSR, with foreign ownership demonstrating the most substantial influence, followed by institutional and managerial ownership. These results affirm that external and institutional stakeholders drive firms toward enhanced CSR practices, aligning with stakeholder and legitimacy theories. The study concludes that ownership structure plays a critical role in shaping CSR strategies and transparency levels among oil and gas companies in Nigeria. Based on these findings, the study recommends that firms develop strategic frameworks to attract and retain foreign investors by aligning CSR practices with global sustainability standards. This will not only improve social responsibility outcomes but also enhance competitiveness and investor confidence in the Nigerian oil and gas sector.